Prevalence of Escherichia coli O157:H7 in cow-calf herds in Kansas - Sargeant, J.M.; Gillespie, J.R.; Hyatt, D.R.; Galland, J.C.; Bohra, L.K.; Oberst, Richard D.; Phebus, Randall K.; Hays, Michael P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Fecal samples from cows and calves and samples of water sources were collected monthly for 8 months from 10 Kansas cow-calf farms to determine the prevalence of E. coli O157:H7. The bacterium was found in 8% of fecal samples from cows that were within 24 hours of calving, 1.4% of fecal samples from cows which were not within 24 hours of calving, 1.4% of calf fecal samples, and 1.5% of water samples. E. coli O157:H7 was identified from at least one sample on all farms.
Keywords: Beef; Cow-calf herds; E. coli O157:H7; Bacterial infection